Some integral properties in the theory of generalized k-Bessel matrix functions - Khammash, Ghazi S.; Shehata, Ayman; Cattani, Carlo (Journal of Innovative Applied Mathematics and Computational Sciences, 2025)
The main purpose of this article is to define some original properties in the theory of the generalized modified k-Bessel matrix functions. These special functions, defined in terms of Wright matrix functions, are generalized and their properties studied in depth. Moreover, it is shown their application to the analysis of certain generalized integral formulas involving the generalized modified k-Bessel matrix function.